Robotic distal pancreatectomy, a novel standard of care? First benchmark values for surgical outcomes from 14 international expert centers. (1st June 2022) - Müller, P; Breuer, E; Tschuor, C; Saint-Marc, O; Keck, T; Coratti, A; De Oliveira, M; Allen, P; Giulianotti, P; Oberkofler, C; Nickel, F; Groot Koerkamp, B; et al.
Abstract: Objective: Robotic distal pancreatectomy (DP) is emerging as the preferred treatment for body and tail tumors of the pancreas. To enable conclusive comparisons with the standard open or laparoscopic approaches and robotic surgery among centers, novel benchmark outcome values are urgently needed. Therefore, the aim of this study was to identify benchmark values from expert centers beyond the learning curve. Methods: This multicenter study analyzed outcomes from consecutive patients undergoing robotic DP for resectable malignant or benign lesions from 14 international expert centers. After the learning curve, defined as the first 10 cases of robotic DP, all consecutive patients were included from the start of the program up to June 2020 with a minimum follow-up of 1 year. Benchmark patients were those without significant comorbidities including obesity (BMI >35 kg/m2) cardiac disease, chronic pulmonary disease. Benchmark cutoff values were derived from the 75th or the 25th percentile of the median values of all benchmark centers. Results: After reaching the learning curve, 289 (47%) of a total of 614 consecutive patients qualified as benchmark cases. The proportion of benchmark patients varied between 24%-64% per center. Benchmark cut-offs showed a low 6 month- postoperative mortality (<0.6%), but high overall morbidity (<58.3%). Benchmark cutoffs for operative time (<300 min), conversion rate (<3%), clinically relevant pancreatic fistulas (<26.9%), CCI at 90-days (<14.8), hospital stay (<7 days) and readmission rate (<22.9%). Benchmark cut-offs for complications remained unchanged after 3 months follow-up. For ductal adenocarcinoma benchmark cutoffs for number of lymph nodes were > 19 with an R0 resection rate of > 85%, and an overall survival of >86% and >52% after 1- and 5-years, respectively. Centers with a low cohort of benchmark patients (more difficult cases) had less clinically relevant pancreatic fistula (9% vs. 23%) and less overall complications (32% vs. 48%). Conclusion: This benchmark analysis sets novel reference values for robotic DP, indicating favorable outcomes as compared to laparoscopic and open DP. These references values may serve for quality control of surgery in centers embarking in robotic DP, and include the procedure in the standard of care.